Colourimetric detection of Ag(i) ions using dCTP-stabilised gold nanoparticles. Issue 3 (19th December 2014) - Yang, Chun-Guang; Zhang, Miao; Xu, Zhang-Run
Abstract : A simple colourimetric detection method for Ag(i ) ions based on dCTP-stabilised gold nanoparticles is proposed. Abstract : This work presented a simple colourimetric method for Ag(i ) ion detection based on gold nanoparticles (AuNPs) with unique distance-dependent optical properties. It was the first time that the determination of Ag(i ) ions by inducing the aggregation of dispersed dCTP-stabilised AuNPs was reported. Unlike DNA-functionalised AuNP-based colourimetric approaches, this method did not require the design and synthesis of DNA strands to functionalise AuNPs, which simplified the operation process and reduced the cost. The method was validated by recovery tests using tap water and river water samples; it exhibited high sensitivity and selectivity attributed to the strong and specific binding between Ag(i ) ions and dCTPs. The present strategy provides a good candidate for the colourimetric sensing of Ag(i ) ions in environmental water samples.